Antibacterial carbon dots/iron oxychloride nanoplatform for chemodynamic and photothermal therapy - Yan, Xiang; Yang, Jie; Wu, Juan; Su, Han; Sun, Guowen; Ni, Yanhong; Sun, Weibin (Colloid and interface science communications, 2021)
The inflammatory outbreak caused by abundant bacteria propagation in the infected wound area pose a considerable challenge to human health. To overcome this situation, here the therapeutic method is based on inspired chemodynamic therapy (CDT) induced by a novel iron oxychloride nanosheets (FeOCl NSs) catalyst with hydrogen peroxide (H2O2) and photothermal therapy (PTT) mediated by coating inorganic carbon dots (CDs) and organic polyethylene glycol (PEG) with near-infrared (NIR) emission. The redox cycle of ions on FeOCl NSs enables the generation of facile hydroxyl radical (·OH) from H2O2 activation for further CDT and induces bacteria death. CDs have been set as promising in vivo therapeutic agents due to their excellent biosafety and high photostability. In this study, the nanocomposites FeOCl@PEG@CDs NCs are synthesized by coating the PEG and CDs on the FeOCl NSs, exhibiting a potent PTT responsive effect with 808 nm NIR laser, which highly enhances the antibacterial effect in the infected wound area. The FeOCl@PEG@CDs NCs were prepared for precise PTT and CDT synergistic therapy of bacterial infection during the wound healing process. The developed FeOCl@PEG@CDs NCs integrates the merits of the improved selectivity of Fe(II) toward •OH generation rather than conversion to Fe(IV) and specific heating directly to bacteria. [Display omitted] •The redox cycle of ions on FeOCl NSs enables the generation of ·OH from H2O2.•FeOCl NSs that exhibits a potent PTT responsive effect with 808 nm NIR laser.•PTT and CDT synergistic therapy enables more intelligent platforms for wound healing.